Harvesting sustainability : Strategies for sustainable agriculture in a changing climate - Amanullah, Dr., (Life Sciences E-Books Online, Collection 2026., 2025)
Harvesting sustainability: Strategies for sustainable agriculture in a changing climate by Professor Dr. Amanullah is an essential guide to modern agriculture, tackling the urgent challenges of climate change, food security, and environmental sustainability. This insightful book explores innovative, eco-friendly farming techniques, resilient cropping systems, and resource-efficient practices that enhance productivity while preserving natural ecosystems. Grounded in extensive research and practical solutions, it equips students, educators, researchers, and policymakers with strategies to mitigate climate impacts and ensure long-term agricultural resilience. A must-read for those committed to a sustainable future, this book serves as a roadmap for global food security and environmental stewardship.